2021
DOI: 10.1371/journal.pone.0255440
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 related posttraumatic stress disorder in children and adolescents in Saudi Arabia

Abstract: Introduction The COVID-19 pandemic resulted in quarantine/lockdown measures in most countries. Quarantine may create intense psychological problems including post-traumatic stress disorder (PTSD) especially for the vulnerable critically developing children/adolescents. Few studies evaluated PTSD associated with infectious disasters but no Saudi study investigated PTSD associated with COVID-19 in children/adolescents. This study was undertaken to screen for PTSD in children/adolescent in Saudi Arabia to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 25 publications
5
29
0
1
Order By: Relevance
“…Similarly, a Saudi-Arabia-based study reported that one-third of the children in its sample experienced mild levels of post-traumatic stress due to COVID-19-related quarantine/lockdown measures [28]. In congruence with these findings, the present study found that children not diagnosed with COVID-19 and/or not required to quarantine appeared calmer, more thoughtful, and more emotionally stable.…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, a Saudi-Arabia-based study reported that one-third of the children in its sample experienced mild levels of post-traumatic stress due to COVID-19-related quarantine/lockdown measures [28]. In congruence with these findings, the present study found that children not diagnosed with COVID-19 and/or not required to quarantine appeared calmer, more thoughtful, and more emotionally stable.…”
Section: Discussionsupporting
confidence: 83%
“…In the 2021 investigation by Liu and colleagues [6], 18.4% of children who had been hospitalized for COVID-19 experienced clinically significant PTSD, but this study assessed a small convenience sample that may not be representative of all children with COVID-19. A study conducted 2 months after widespread lockdown in Saudi Arabia assessed PTSD in a random national sample of children (7 to 18 years of age) in which COVID-19 illness of the child or close relative and COVID-19 death of a close relative or friend were reported by 3.7% and 3.9%, respectively [10]. Potential PTSD was identified in 13.0% of the sample [10].…”
Section: Posttraumatic Stress Disordermentioning
confidence: 99%
“…A study conducted 2 months after widespread lockdown in Saudi Arabia assessed PTSD in a random national sample of children (7 to 18 years of age) in which COVID-19 illness of the child or close relative and COVID-19 death of a close relative or friend were reported by 3.7% and 3.9%, respectively [10]. Potential PTSD was identified in 13.0% of the sample [10]. In a longitudinal population-based investigation in the United Kingdom (U.K.), Wright and colleagues [11 •] revealed increased PTSD symptoms 3 months after distancing measures were initiated relative to an earlier assessment from December to March 2020.…”
Section: Posttraumatic Stress Disordermentioning
confidence: 99%
“…A review of exposure characteristics, PTSD rates, and the assessment of diagnostic criteria in six COVID-19 studies that assessed PTSD in general child populations 3 , 4 , 5 , 6 , 7 , 8 evidenced the concerns raised in the adult literature. 1 Only two papers provided much detail on participants’ COVID-19 experiences or exposure, 5 , 6 and none clearly limited the diagnosis of PTSD to participants who met the exposure criterion. In a sample with a sizeable number of children who knew someone who tested positive for, or died of, COVID-19, 45% scored above the study’s threshold for PTSD.…”
mentioning
confidence: 99%